2007
DOI: 10.1039/b707326g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan membrane surface modification via plasma induced polymerization on the adhesion of osteoblast-like cells

Abstract: The surface of solvent cast chitosan membranes was modified using a two-step procedure. Oxygen plasma treatment was used at the first activation step followed by vinyl monomer graft polymerization. Two monomers were used in order to compare the influence of different functional groups on cell adhesion and proliferation; acrylic acid (AA) was used to introduce carboxyl groups and vinyl sulfonic acid (VSA) was used as a source of sulfonic groups. The surface chemistry/energy changes were characterized by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 20 publications
14
99
0
1
Order By: Relevance
“…The few viable cells adhered on the CTS sample surface after 10 days of culture did not present the typical fibroblast-like morphology, being quite round and sparsely distributed. The poor cell adhesion and proliferation on chitosan membranes have been previously reported (Lopez-Perez et al, 2007;Zhu et al, 2005). The iPrOH50 membranes presented very similar results (not shown).…”
Section: Cell Sheet Detachment and Assessment Of The Cell Viabilitysupporting
confidence: 89%
See 3 more Smart Citations
“…The few viable cells adhered on the CTS sample surface after 10 days of culture did not present the typical fibroblast-like morphology, being quite round and sparsely distributed. The poor cell adhesion and proliferation on chitosan membranes have been previously reported (Lopez-Perez et al, 2007;Zhu et al, 2005). The iPrOH50 membranes presented very similar results (not shown).…”
Section: Cell Sheet Detachment and Assessment Of The Cell Viabilitysupporting
confidence: 89%
“…As our aim is to be able to create cell sheets, which can be harvested by simply lowering the temperature, cell confluence is a critical parameter to achieve. In one of our previous works (Lopez-Perez et al, 2007), plasma treatment was very effective on improving the viability and proliferation of osteoblast-like cells. It is wellknown that the surface energy has a striking effect on the cell behavior.…”
Section: Cell Sheet Detachment and Assessment Of The Cell Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The identities of different surfaces were further confirmed by water contact angle data as it has been shown that surface wettability is directly related to the surface energy and it is a useful parameter to correlate with cell-biomaterial interactions on the interface [33,34]. As demonstrated in Table 1, both advancing and receding water contact angles change after each step of chemical reaction and photoactivation, suggesting possible surface composition changes.…”
Section: Surface Characterizationsupporting
confidence: 51%